Chapter III: the religious buildings / Nur Atiqah Husaini and Syamimi Liyana Amat Rais - Husaini, Nur Atiqah; Amat Rais, Syamimi Liyana (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Learning how Masjid Jami or also known as Sultan Syarif Abdurrahman Mosque used to call people to prayer by getting on the upper floor of the mosque to informed inform the villagers that it was time for prayer shows that even with deficiency of technology, they still try to fulfill what needs to be accomplished by doing the obligatory prayers wherever they can. It inspires me that people still work hard to fulfill their duty and responsibility even with difficulty.